The Mediterranean Muslim Navy and the Expeditions Dispatched against Constantinople - Zampaki, Theodora (Richtmann Publishing, 2012)
The aim of this paper is to present an account of the information we find in various Arabic sources of the early periodof Arabic historiography on the preparation of a military naval force and the expeditions launched against Constantinople duringthe period of the early expansion of the Muslim Arabs. Arabic sources give various pieces of information on shipyards, ports aswell the recruitment of local men both in Syria and Egypt in the preparation of a military fleet by the Arab Muslim leaders. TheByzantine naval military bases in Syria and Egypt were taken by the Arabs in the early 7th century, and local men who servedthe Byzantines before, then joined the Arabs. These Arab naval forces were not only engaged in a maritime conflict with theByzantine fleet in the East Mediterranean but also took part both in the expeditions launched against Byzantine territories andespecially in the early sieges of Constantinople, the ultimate aim of all preparations. For the Arabs, the significance ofConstantinople was based not only ô€ˆ n its political and cultural prestige but also ô€ˆ n its material affluence. For this reason, fourtimes it was the aim of Arab Muslim forces sent by Arab leaders in Damascus of Syria. Indeed, the Arab navy played animportant role in the East Mediterranean conflict and the expeditions against Constantinople, which are celebrated both inMuslim history and legend, have found their way into the Muslim eschatological literature as well.